Differences in Language Policies of Chinese-inhabited Southeast Asian Countries - Kironská, Kristína (Advances in Social Sciences Research Journal, 2015)
Language is a tool that governments use to create national identity. Language policies are not static and with the impact of several factors can shift over time. With the influx of new immigrants, both the ethnic and linguistic structures of countries change, as had been the case with the Chinese immigrants who arrived in Southeast Asia in two big waves, in the 15th/16th and later in the 19th/20th century and made it their new home. Today, some 30 million overseas Chinese live in Southeast Asia, most prominently in Malaysia, the Philippines, Singapore, Indonesia, Thailand, Myanmar, and in Vietnam. Some of these countries pursue monolingual policies, while others have opted for multilingualism. This article explains the differences in regard of the presence or absence of the Chinese language in the language policies of Southeast Asian countries with a substantial Chinese minority. First of all, authoritarian regimes are generally associated with less minority language recognition, and thus the Chinese language is less likely to be included in the official language apparatus in a dictatorship. Second, if the Chinese minority is included in the government, it is more likely that the Chinese language be either one of the official languages, or one of the languages of instruction, or both. And third, the bigger and more coherent the Chinese minority, the bigger the chance of the Chinese language being part of the national language policy. The author has identified three variables that influence the Chinese language participation in the language policy of a country, namely the country’s regime type, the size and cohesion of the Chinese minority living in that country, and the Chinese minority’s access to the national government. The approach used in this article is both descriptive and analytical, and offers a comparative review of the language policy structures of various countries throughout Southeast Asia in regard of the Chinese language.